2013
DOI: 10.1038/nrneurol.2013.209
|View full text |Cite
|
Sign up to set email alerts
|

NURR1 in Parkinson disease—from pathogenesis to therapeutic potential

Abstract: In Parkinson disease (PD), affected midbrain dopamine (DA) neurons lose specific dopaminergic properties before the neurons die. How the phenotype of DA neurons is normally established and the ways in which pathology affects the maintenance of cell identity are, therefore, important considerations. Orphan nuclear receptor NURR1 (NURR1, also known as NR4A2) is involved in the differentiation of midbrain DA neurons, but also has an important role in the adult brain. Emerging evidence indicates that impaired NURR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
213
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(224 citation statements)
references
References 105 publications
7
213
1
3
Order By: Relevance
“…Although the presence of o-αSyn was not disclaimed in these studies, we advance that these changes might be a result of the presence of αSyn oligomers based on our own in vitro results. Using predictive databases, we found that human and mouse SYN1 and SYN2 promoters contained conserved putative responsive elements for CREB and Nurr1, respectively, two transcription factors involved in αSyn-mediated toxicity (29,30,63). We then found that the protein abundance of pS133-CREB and Nurr1 was decreased in association with the age-dependent accumulation of αSyn oligomers in TgI2.2 mice and following intraneuronal delivery of o-αSyn.…”
Section: Dependence On Endogenous αSyn For Exogenous O-αsyn To Inducementioning
confidence: 87%
“…Although the presence of o-αSyn was not disclaimed in these studies, we advance that these changes might be a result of the presence of αSyn oligomers based on our own in vitro results. Using predictive databases, we found that human and mouse SYN1 and SYN2 promoters contained conserved putative responsive elements for CREB and Nurr1, respectively, two transcription factors involved in αSyn-mediated toxicity (29,30,63). We then found that the protein abundance of pS133-CREB and Nurr1 was decreased in association with the age-dependent accumulation of αSyn oligomers in TgI2.2 mice and following intraneuronal delivery of o-αSyn.…”
Section: Dependence On Endogenous αSyn For Exogenous O-αsyn To Inducementioning
confidence: 87%
“…Specifically, the differential expression patterns for the neurotrophic factors determined by quantitative PCR (qPCR) ( Figure 3N) were similarly replicated in the RNA-seq analyses ( Figure 4E), indicating fidelity of the RNAmDA neurons are specified based on the expression of several midbrain-specific genes, such as Nurr1, Foxa2, Lmx1a/b, Pitx3, and En1/2. As these midbrain markers play critical roles in DA phenotype maintenance, survival, and function (36)(37)(38)(39), their expression is critical in the preparation of mDA neurons for therapeutic purposes. However, we and others have recently shown that the expression of midbrain-specific markers in mDA neurons is largely affected by in vitro and in vivo environments and thus easily lost during passages, long after differentiation in vitro and after transplantation in vivo (16,40,41).…”
Section: Resultsmentioning
confidence: 99%
“…In the niche established by the VM-Ast, grafted NPCs efficiently differentiated into morphologically, synaptically, and functionally mature mDA neurons and the differentiated mDA neuronal cells survived for long periods after transplantation while maintaining expression of midbrain-specific markers. The expression of midbrain-specific factors such as Nurr1 and Foxa2 is a critical indicator for successful mDA neuron engraftment (49), as the expression of these genes is required for mDA neuron survival, function, and phenotype maintenance (36)(37)(38)(39). Considering that the expression of midbrain factors is easily lost in stressful conditions (16,40,41), sustained expression of midbrain markers in the presence of astrocytes is likely to be attained by the observed astrocyte actions that change the hostile inflammatory host brain milieu into a neurotrophic environment.…”
Section: Cografting Of Astrocytes Potentiates the Cell Therapeutic Efmentioning
confidence: 99%
“…A reduction in the electrical activity and of the excitability of DA neurons seems to augment their propensity to degenerate 12 . Nevertheless, the complexity of PD pathogenesis requires further studies to identify the mechanisms involved in DA neurons degeneration [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%